Iterative optimization in inverse problems - Byrne, Charles L. 1947- (CRC Press, 2014)
"This book covers iterative optimization methods that stems from inverse problems and related issues. The author presents the theoretical side of inverse methods and as a result ignores discrete problems, stochastic methods, and combinatorial optimization. The coverage moves from an introduction of auxiliary function methods to a discussion of several examples of auxiliary fixed (AF) point methods in optimization to consideration of related topics such as operator fixed point methods. A few problems have been scattered throughout the book so that it might be used in a special topics class on optimization at the graduate level"--
Includes bibliographical references and index. - Print version record
Keywords: Iterative methods (Mathematics); Algorithms; Inverse problems (Differential equations); Computer algorithms; Itération (Mathématiques); Algorithmes; Problèmes inverses (Équations différentielles); algorithms; MATHEMATICS; Calculus; MATHEMATICS; Mathematical Analysis; Inverses Problem; Optimierung; Iteration